Use of Immobilized Amine Transaminase from Vibrio fluvialis under Flow Conditions for the Synthesis of (S)‐1‐(5‐Fluoropyrimidin‐2‐yl)‐ethanamine. Issue 5 (22nd January 2020) - Semproli, Riccardo; Vaccaro, Gianmarco; Ferrandi, Erica E.; Vanoni, Marta; Bavaro, Teodora; Marrubini, Giorgio; Annunziata, Francesca; Conti, Paola; Speranza, Giovanna; Monti, Daniela; Tamborini, Lucia; Ubiali, Daniela
Abstract: We report on the covalent immobilization of the ( S )‐selective amine transaminase from Vibrio fluvialis ( Vf ‐ATA) and its use in the synthesis of ( S )‐1‐(5‐fluoropyrimidin‐2‐yl)‐ethanamine, a key intermediate of the JAK2 kinase inhibitor AZD1480. Immobilized Vf ‐ATA on glyoxyl‐agarose (activity recovery: 30 %) was used in a packed‐bed reactor to set‐up a continuous flow biotransformation coupled with a straightforward in‐line purification to circumvent the 2‐step process described in literature for the batch reaction. The newly developed biotransformation was run in a homogeneous system including dimethyl carbonate as a green co‐solvent. Optically pure ( S )‐1‐(5‐fluoropyrimidin‐2‐yl)‐ethanamine (ee >99 %) was isolated in 35 % yield. Abstract : All‐in‐One : The amine transaminase from Vibrio fluvialis ( Vf ‐ATA) was covalently immobilized and used in the synthesis of ( S )‐1‐(5‐fluoropyrimidin‐2‐yl)‐ethanamine (3 ) in a flow system. Coupling of the continuous flow biotransformation with an in‐line purification step resulted in a highly productive and straightforward bioprocess.